Influence of Indentation on the Fatigue Strength of Carbonitrided Plain Steel - Jiewei Gao; Guangze Dai; Junwen Zhao; Hengkui Li; Lei Xu; Zhenyu Zhu (Advances in Materials Science and Engineering)
To study the influence of indentation on the fatigue strength of untreated and carbonitrided specimens of S38C steel, the fatigue limit of specimens with and without indentations was tested. Fracture surfaces were observed using scanning electron microscopy (SEM). The results show that the fatigue strength of the untreated specimen decreases with increasing dimension of indentation, without significant difference compared to the predicted results. Compared to the fatigue limit of the untreated specimen, those of the carbonitrided specimen and the carbonitrided specimen whose compound layer was polished were improved by 12% and 40%, respectively. The fatigue strength of the carbonitrided specimen decreased sharply with increasing indentation size because of the presence of microcracks in the compound layer. When the compound layer was removed, the fatigue limit was observed to be less sensitive to indentation than that of the carbonitrided specimen.